INVENTARISASI POTENSI CAGAR BUDAYA PENINGGALAN MASA PENJAJAHAN BELANDA SEBAGAI SUMBER BELAJAR SEJARAH LOKAL DI KECAMATAN BEKRI KABUPATEN LAMPUNG TENGAH TAHUN 2019 - Ardi Bangun Praseyo; Umi Hartati (Swarnadwipa, 2019)
Cultural Heritage is a heritage that needs to be preserved, but in reality there are still many people who do not have the awareness to maintain and care for the potential of cultural heritage as a national cultural heritage. The purpose of this study is to describe the potential of cultural heritage from the Dutch colonial era in Bekri District, Central Lampung Regency and to describe the inventory of the Dutch colonial heritage which can be used as a source of local history. The approach of this research is qualitative research. This research method uses descriptive research method. This research was conducted at PTPN VII Bekri District, Central Lampung Regency. Data in this research were obtained through interview and observation methods. Data analysis techniques using descriptive analysis techniques. The results of this study that the potential of cultural preservation is any power that can be developed from objects / objects. Thepotential of cultural heritage in PTPN VII Bekri Subdistrict, Central Lampung Regency, namely, long beds, chimneys, digester machines, manager houses, wells, art buildings, houses on stilts, bathrooms, public toilets, and afdeling counters. The building is a potential cultural heritage in the Bekri District, Central Lampung Regency, especially in the scope of PTPN VII. The potential of the cultural heritage can be used as a source of local history which is a legacy during the Dutch colonial period. It contains important values in the lives of the Bekri community and surrounding areas.